Self-Study Results of Genetics Module Based on Learning Management System Among Medical Students of Universitas Riau - Zulharman; Rahmat Azhari Kemal; Riki Sukiandra; Bayu Fajar Pratama (Future Science, 2022)
The Genetics module based on a learning management system (LMS) is a standalone website with an instructional design for self-study about genetic literacy. This module is expected to be useful for medical students of Universitas Riau (FK UNRI) from various class years to study at any time. The purpose of this study was to find comparative results of self-study of genetic modules based on LMS among UNRI's medical students in various class years and to determine effectiveness of genetics module based on learning management system among medical students of Universitas Riau. The research method was quantitative. The subjects were 34 UNRI's medical students who were taken proportionally from three class years. The research data was obtained using the UNC-GKS questionnaire. The results showed that the average pre-test scores for the first, second, and third years were 58, 58, and 63. The statistical test results for comparing the pre-test scores of these three class years gave no significant difference. The results of the average post-test scores for the first, second and third years were 58, 68, and 68. The results of the statistical test comparing the post-test scores of these three class years gave no significant difference also. The results of the Wilcoxon test was p < 0.02 which means that there was an increase in genetic literacy scores after FK UNRI students take genetic modules based on the learning management system for independent learning at FK UNRI. The conclusion was the self-study of the genetic module based on the LMS among UNRI's medical students gave no significant difference when viewed from the difference in the year of class. There was an increase in genetic literacy scores after FK UNRI students take a genetic module based on the learning management system for independent learning at FK UNRI. Therefore, UNRI 's medical students can study genetics module based on learning management system from various class years and at any time.